Rare-earth doped fluoride phosphate glasses: Structural foundations of their luminescence properties - Galleani, Gustavo [UNESP]; Santagneli, Silvia Helena [UNESP]; Messaddeq, Younes [UNESP]; De Oliveira, Marcos; Eckert, Hellmut (Royal Society of Chemistry (RSC), 2017)
We report a detailed structural investigation of a series of fluoride-phosphate glasses with different phosphate/fluoride ratios in the system xSr(PO3)2-(100 - x)[AlF3-CaF2-SrF2-MgF2] with x = 5, 10, 20, 40. Raman and multinuclear solid NMR spectroscopies confirm that the polyphosphate network structure is successively transformed to a structure dominated by Al-O-P linkages with increasing AlF3 content. Average numbers of Al-O-P linkages have been quantified by 27Al/31P NMR double-resonance techniques. The majority of the fluoride species are found in an alkaline earth metal/aluminum rich environment. The local environments for rare-earth ions have been characterized by EPR spectroscopy of Yb3+ ion spin probes and by photoluminescence experiments on Eu3+ dopant ions, including the 5D0 → 7F2 and 5D0 → 7F1 transition intensity ratio, the normalized phonon sideband intensities in the excitation spectra, and the lifetime of the 5D0 excited state. The results indicate clear correlations between these parameters as a function of composition, and confirm that even at the highest fluoride levels, there is still some residual rare-earth phosphate coordination.